Exercise-Induced Hemostatic Changes: A Review of Acute Responses and Chronic Adaptations in Endurance Athletes - Graczyk, Natalia; Graczyk, Martyna; Wisoky, Wiktor; Czapla, Natalia; Ziółkowska, Weronika; Strużyńska, Ewelina; Łopińska, Joanna; Majchrzycka, Marta; Ignyś, Piotr; Majchrzak, Mateusz (Journal of Education, Health and Sport, 2026)
Background. Endurance exercise exerts complex effects on the human hemostatic system. Acute bouts of strenuous exercise may transiently induce a prothrombotic state, while habitual endurance training is associated with improved vascular health and reduced baseline thrombotic risk. Aim. To synthesize current evidence on acute and chronic exercise-induced hemostatic responses in endurance athletes and to evaluate their implications for venous thromboembolism (VTE) risk. Material and methods. A narrative literature review was conducted using searches of PubMed, Scopus, Web of Science, and the Cochrane Library up to March 2026 using combinations of keywords related to hemostasis, coagulation, fibrinolysis, endurance training, and athletes. Results. Acute endurance exercise increases platelet activation, thrombin generation, and coagulation factor activity, accompanied by parallel but often insufficient activation of fibrinolysis. In contrast, long-term endurance training promotes adaptive antithrombotic mechanisms, including improved endothelial function, enhanced fibrinolytic capacity, and reduced platelet reactivity. Factors such as genetic predisposition, dehydration, environmental stressors, travel, and age further modulate these responses and may increase thrombotic susceptibility in certain athletes. Preventive strategies, including optimized hydration, training periodization, biomarker monitoring, and targeted pharmacological prophylaxis for high-risk individuals, may mitigate exercise-associated thrombotic events. Conclusions. Endurance exercise induces a biphasic hemostatic pattern characterized by transient procoagulant responses superimposed on long-term protective adaptations. Understanding this physiological paradox is essential for developing evidence-based recommendations that support safe participation in endurance sports.